Optimising Follicular Development, Pituitary Suppression, Triggering and Luteal Phase Support During Assisted Reproductive Technology: A Delphi Consensus - Orvieto, Raoul; Venetis, Christos A.; Fatemi, Human M.; D’Hooghe, Thomas; Fischer, Robert; Koloda, Yulia; Horton, Marcos; Grynberg, Michael; Longobardi, Salvatore; Esteves, Sandro C.; Sunkara, Sesh K.; Li, Yuan; et al. (Frontiers in Endocrinology, 2021)
Background: A Delphi consensus was conducted to evaluate global expert opinions on key aspects of assisted reproductive technology (ART) treatment. Methods: Ten experts plus the Scientific Coordinator discussed and amended statements plus supporting references proposed by the Scientific Coordinator. The statements were distributed via an online survey to 35 experts, who voted on their level of agreement or disagreement with each statement. Consensus was reached if the proportion of participants agreeing or disagreeing with a statement was >66%. Results: Eighteen statements were developed. All statements reached consensus and the most relevant are summarised here. (1) Follicular development and stimulation with gonadotropins (n=9 statements): Recombinant human follicle stimulating hormone (r-hFSH) alone is sufficient for follicular development in normogonadotropic patients aged <35 years. Oocyte number and live birth rate are strongly correlated; there is a positive linear correlation with cumulative live birth rate. Different r-hFSH preparations have identical polypeptide chains but different glycosylation patterns, affecting the biospecific activity of r-hFSH. r-hFSH plus recombinant human LH (r-hFSH:r-hLH) demonstrates improved pregnancy rates and cost efficacy versus human menopausal gonadotropin (hMG) in patients with severe FSH and LH deficiency. (2) Pituitary suppression (n=2 statements): Gonadotropin releasing hormone (GnRH) antagonists are associated with lower rates of any grade ovarian hyperstimulation syndrome (OHSS) and cycle cancellation versus GnRH agonists. (3) Final oocyte maturation triggering (n=4 statements): Human chorionic gonadotropin (hCG) represents the gold standard in fresh cycles. The efficacy of hCG triggering for frozen transfers in modified natural cycles is controversial compared with LH peak monitoring. Current evidence supports significantly higher pregnancy rates with hCG + GnRH agonist versus hCG alone, but further evidence is needed. GnRH agonist trigger, in GnRH antagonist protocol, is recommended for final oocyte maturation in women at risk of OHSS. (4) Luteal-phase support (n=3 statements): Vaginal progesterone therapy represents the gold standard for luteal-phase support. Conclusions: This Delphi consensus provides a real-world clinical perspective on the specific approaches during the key steps of ART treatment from a diverse group of international experts. Additional guidance from clinicians on ART strategies could complement guidelines and policies, and may help to further improve treatment outcomes.